The consistency of force and movement variables as an indicator of rowing performance - Doyle, M.; Lyttle, A.; Elliott, B. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
A portable biomechanical collection system was used to test fourteen male, coxless pair rowing crews under simulated race speeds. The data was used to examine if the consistency of 8 biomechanical variables, calculated using a modified Coefficient of Variation (CoV), were related to the overall performance, in terms of velocity, of the crews. It was found that 6 of the variables demonstrated a significant correlation to overall boat speed, with the consistency of Normal Gate Force (r=0.737), Handle Velocity (r=0.758) and Trunk Velocity (r=.757) showing very strong correlation. It was concluded that while not imperative to the outcome, consistency of force application and movement patterns may be important in rowing performance.